Gallic Acid Reverses Neurochemical Changes Induced by Prolonged Ethanol Exposure in the Zebrafish Brain. (10th February 2021) - Agostini, Jotele Fontana; Santo, Glaucia Dal; Baldin, Samira Leila; Bernardo, Henrique Teza; de Farias, Ana Caroline Salvador; Rico, Eduardo Pacheco; Wanderley, Almir Gonçalves
Highlights: Gallic acid positively modulates cholinergic damage caused by exposure to ethanol. Gallic acid in isolation increases antioxidant activity in the zebrafish brain. Oxidative stress induced by ethanol is regulated positively by gallic acid. Abstract: Gallic acid (GA) is a polyphenolic compound that has attracted significant interest due to its antioxidant action through free radical elimination and metal chelation. Ethanol is a highly soluble psychoactive substance, and its toxicity is associated with oxidative stress. In this context, the purpose of the present study was to investigate the effect of GA on neurochemical changes in zebrafish brains exposed to ethanol. GA was first analyzed in isolation by treating the animals at concentrations of 5, 10, and 20 mg/L for 24 h and 48 h. The results revealed that the group exposed to 20 mg/L over a 24/48 h period exhibited increases in thiobarbituric acid reactive substance (TBA-RS) levels and 2′, 7′-dichlorofluorescein (DCFH) oxidation, demonstrating a pro-oxidant profile. Moreover, decrease in acetylcholinesterase (AChE) enzyme activity was observed. To investigate the effects of GA after ethanol exposure, the animals were divided into four groups: control; those exposed to 0.5% ethanol for 7 days; those exposed to 0.5% ethanol for 7 days and treated with GA at 5 and 10 mg/L on day 8. Treatment with GA at 5 and 10 mg/L reversed impairment of choline acetyltransferase activity and the damage to TBA-RS levels, DCFH oxidation, and superoxide dismutase activity induced by ethanol. Results of the present study suggest that GA treatment (20 mg/L) appeared to disrupt oxidative parameters in the zebrafish brain. GA treatment at 5 and 10 mg/L reversed alterations to the cholinergic system induced by prolonged exposure to ethanol in the zebrafish brain, probably through an antioxidant mechanism.